Liver X receptor beta deficiency attenuates autoimmune-associated neuroinflammation in a T cell-dependent manner. Issue 124 (November 2021) - Bogie, Jeroen F.J.; Vanmierlo, Tim; Vanmol, Jasmine; Timmermans, Silke; Mailleux, Jo; Nelissen, Katherine; Wijnands, Erwin; Wouters, Kristiaan; Stinissen, Piet; Gustafsson, Jan-Åke; Steffensen, Knut R.; Mulder, Monique; et al.
Abstract: The initiation and progression of autoimmune disorders such as multiple sclerosis (MS) is linked to aberrant cholesterol metabolism and overt inflammation. Liver X receptors (LXR) are nuclear receptors that function at the crossroads of cholesterol metabolism and immunity, and their activation is considered a promising therapeutic strategy to attenuate autoimmunity. However, despite clear functional heterogeneity and cell-specific expression profiles, the impact of the individual LXR isoforms on autoimmunity remains poorly understood. Here, we show that LXRα and LXRβ have an opposite impact on immune cell function and disease severity in the experimental autoimmune encephalomyelitis model, an experimental MS model. While Lxrα deficiency aggravated disease pathology and severity, absence of Lxrβ was protective. Guided by flow cytometry and by using cell-specific knockout models, reduced disease severity in Lxrβ -deficient mice was primarily attributed to changes in peripheral T cell physiology and occurred independent from alterations in microglia function. Collectively, our findings indicate that LXR isoforms play functionally non-redundant roles in autoimmunity, potentially having broad implications for the development of LXR-based therapeutic strategies aimed at dampening autoimmunity and neuroinflammation. Highlights: LXRα and LXRβ oppositely impact autoimmune-associated neuroinflammation. LXRβ deficiency reduces neuroinflammation and disease severity in the EAE model. Changes in microglia physiology do not account for protective impact LXRβ deficiency. Absence of LXRβ ameliorates EAE disease severity in a T cell-dependent manner.